THE EFFECT OF PROBLEM-BASED LEARNING ON MATHEMATICS LEARNING OUTCOMES CONTROLLING FOR STUDENTS’ NUMERICAL ABILITY - Made Sri Astika Dewi; I Komang Sesara Ariyana; Putu Gede Asnawa Dikta; Made Padmarani Sudewi Putri (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Difficulties in understanding mathematical concepts remain a major problem among elementary school students, particularly when learning is dominated by conventional teaching methods that limit critical thinking and problem-solving skills. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model in improving fifth-grade students’ mathematics achievement while controlling for numerical ability as a covariate. A quasi-experimental design with a single-factor independent groups design using covariates was employed. The participants consisted of 74 fifth-grade students from Gugus 5 Bima, comprising 37 students from SDN 1 Baluk as the experimental group taught using PBL and 37 students from SDN 2 Banyubiru as the control group taught using conventional methods. Data were collected using validated and reliable tests of numerical ability and mathematics achievement, and analyzed using ANCOVA after meeting the assumptions of normality, homogeneity, and linearity. The results indicate that students taught using the PBL model achieved significantly higher mathematics scores than those taught using conventional methods (F = 47.334, p < 0.05). Furthermore, after controlling for numerical ability, the PBL model remained significantly more effective in improving students’ mathematics achievement compared to conventional instruction (F = 14.135, p < 0.05). In conclusion, the PBL model is effective in enhancing elementary students’ mathematics achievement and can be recommended as an instructional approach to support deeper conceptual understanding and problem-solving skills.